Theology and society in the second and third centuries of the Hijra - Ess, Josef van, 1934- (Leiden Leiden Leiden Leiden)
5 cilt (1. c. xxi, 545 s. ; 2. c. xii, 844 s. ; 3. c. xi, 555 s. ; 4. c. xvii, 821 s. ; 5. c. 302 s.)